2018
DOI: 10.20344/amp.10135
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Gestacional: Serão os Atuais Critérios de Diagnóstico Mais Vantajosos?

Abstract: The Directorate-General of Health - International Association of Diabetes and Pregnancy Study Groups criteria were associated with a decrease in macrosomia, not accompanied by an improvement of obstetrical/perinatal outcomes. The benefit of using these criteria is open to debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
0
4
0
13
Order By: Relevance
“…It may be recognized that there is a large heterogeneity in AIT use in GDM: ADA prior suggested that AIT was needed in 15–30% of GDM patients (under Carpenter–Coustan or National Diabetes Data Group criteria) and this rate may decrease provided that the IADPSG criteria are implemented [5]. Authors in Germany found a 37% relative increase in anti-diabetic agent use for GDM treatment from 2008 to 2012 [30] and AIT use rates in GDM may be as high as 54.9% even using the IADPSG (2013 WHO) diagnostic criteria according to a recent Portuguese study [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It may be recognized that there is a large heterogeneity in AIT use in GDM: ADA prior suggested that AIT was needed in 15–30% of GDM patients (under Carpenter–Coustan or National Diabetes Data Group criteria) and this rate may decrease provided that the IADPSG criteria are implemented [5]. Authors in Germany found a 37% relative increase in anti-diabetic agent use for GDM treatment from 2008 to 2012 [30] and AIT use rates in GDM may be as high as 54.9% even using the IADPSG (2013 WHO) diagnostic criteria according to a recent Portuguese study [9].…”
Section: Discussionmentioning
confidence: 99%
“…The overall costs of antenatal insulin therapy (AIT) are influenced by the changing GDM diagnostic criteria also. The prevalence of GDM may substantially increase upon implementation of the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) diagnostic criteria [9]. Despite the fact that the relative proportion of GDM patients requiring AIT may be lower using the newer diagnostic criteria compared to the 15–30% suggested earlier by American Diabetes Association (ADA) using the Carpenter–Coustan or National Diabetes Data Group criteria, the total number of GDM patients requiring AIT might still increase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the goal is to reunite the scientific production regarding the theme Gestational Diabetes and report associated factors on the development of the disease. A systematic literature disso, na diabetes mellitus gestacional (DMG), a placenta é responsável pela liberação de um hormônio chamado Hormônio Lactogênio Placentário, (HLP) e outros hormônios anti-insulínicos, são liberados durante a gestação, toda via, estes inibem a ação da insulina, obrigando as células do pâncreas a produzirem mais insulina para que os níveis de glicemia se estabilizem, no entanto se não houver o controle glicêmico, a paciente desenvolverá a diabetes gestacional, comum da 20° à 26° semana de gestação(FERREIRA et al, 2018;MIMOSO, 2017;MIMOSO;.…”
unclassified